If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12/3=6/2(3)+3
We simplify the equation to the form, which is simple to understand
12/3=6/2(3)+3
Simplifying:
+4=6/2*(3)+3
Simplifying:
+4=+3*(3)+3
Reorder the terms in parentheses
+4=+(+9)+3
Remove unnecessary parentheses
+4=+9+3
We move all terms containing to the left and all other terms to the right.
0=+9+3-4
We simplify left and right side of the equation.
0=+8
0=8
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 16t^2-34t+18=0 | | 6x+10x=32 | | x-2(1x+10)=12 | | -0.5y+0.2=0.75y-0.2 | | -8-8x=-55-10x | | 16t^2-128+240=0 | | 1.17+x=2x-1.17 | | 49t^3-4t=0 | | 60-5x=4x+21 | | 9(t-4)+3t=4(3t+4)-12 | | 3+6p=13+6 | | 5x-9x=-24 | | 2p-10=-4(6p+5)+8(-10+3p) | | 5-7x=22-14x | | x^2-17x+72.25=-72+72.25 | | -5s+19=(4+5) | | -9(3x+7)=-8(x-4) | | 92-9=8a | | 6x(x-1)=56-11x | | 34+ds+4-4ds-9876655= | | 12-t=5t | | 34xds+4-4ds-9876655= | | 4(y+5)+4=60 | | 0.67x+1.33=-0.67 | | 5-(x/3)=7 | | 9d-d+4d+6-4d=0 | | 1x-1=5x+3x-8 | | -3z+8+(-12z)=-2 | | 5x+12+x+3x-2=180 | | d+r= | | 2k+5/3+8/3=1/3 | | -3z+8+(-12z)=-12 |